PENGARUH MANAJEMEN LABA, LEVERAGE DAN PROFITABILITAS TERHADAP BOOK-TAX DIFFERENCES (BTD) PADA PERUSAHAAN YANG TERDAFTAR DI JAKARTA ISLAMIC INDEX (JII) - Putri Indahna Irda; Adhisyahfitri Evalina Ikhsan (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2018)
This research is designed to investigate the influence of earnings management, leverage and profitability toward book tax differences of Shariah companies in Indonesia. The samples are consistently listed companies in JII (Jakarta Islamic Index) for period 2012-2015. They are collected based on purposive sampling method. The audited financial reports of the sample companies, as the data, are analyzed by utilizing multiple regression analysis. The finding of this research shows that earnings management, leverage and profitability simultaneously influence book tax differences. Partially, earnings management and profitability have influence towardbook tax differences meanwhile leverage does not.